Effective Strategies for Developing Reading Comprehension - qizi, Shirinqulova Sitora Muzaffar (Research Parks Publishing LLC, 2021)
Reading is an interactive process in which readers construct a meaningful representation of a text using effective reading strategies. Effective reading strategies are considered as significant skills that have received the special focus on students’ reading comprehension proficiency. In this paper, the researchers define the term reading and reading comprehension, explain the types of reading, declare models of reading process, state theories of reading comprehension, review the effective strategies for reading comprehension, and finally mention findings of learners’ reading strategies and their reading comprehension proficiency. The review of literature indicates that reading strategies play a significant role in improving the students’ reading comprehension skill.